39.7k views
5 votes
Can you solve 6r-3=-2(r+1) for me please??!!!!

2 Answers

4 votes

Answer:

r = 1/8

Explanation:

6r-3=-2(r+1)

6r-3 = -2r+-2

(6r+2r)-3=(-2r+2r)+-2

8r-3=-2

8r(-3+3)=-2+3

8r = 1

8r/8 = 1/8

r = 1/8

User AppSolves
by
5.9k points
2 votes

Answer:

1/8

Explanation:

Expand the equation:

6r-3=-2r-2

Add 3 to both sides:

6r-3+3=-2r-2+3

Then Simplify:

6r=-2r+1

Add 2r to both sides:

6r+2r=-2r+1+2r

Simplify again:

8r=1

Divide both sides by 8:

8r/8 = 1/8

Simplify once more:

r = 1/8

User AaronSieb
by
4.9k points